Materials selection for natural fiber reinforced polymer composites using analytical hierarchy process. - Salit, Mohd Sapuan; Zainudin, Edi Syams; Leman, Zulkiflle; Kho, J. Y.; Ahmed Ali, B. A.; Hambali, Ariff (2011)
Material selection is an important process in the product development. To avoid inappropriate decision of materials, analytic hierarchy process (AHP) can be one of the useful tools for determining the most suitable material for automotive dashboard panel. In this project, database of material properties of natural fiber composites has been organized systematically. The material properties of natural fiber material involved are density, Young’s modulus and tensile strength. There are 29 types of natural fiber composites that have been considered in the application of AHP. The most suitable natural fiber composite for automotive dashboard panel is determined by considering main criteria and sub-criteria in the hierarchy model. The final decision was carried out by performing different scenarios of the sensitivity analysis in order to study the effect of the different factors on deciding the most suitable material.